Application of cognitive and behaviour framework module in the treatment for mental games among Golf athletes: A study of UUM National Golf Academy - Omar, Zainudin; Kamsani, Siti Rozaina; Ishak, Noor Azniza; Shaari, Azmi (R.K. Sharma, lntitute of Medico-Legal Publications, 2019)
This article discusses the continued effects of using the counselling approach module, ABC Rational Emotive Behaviour Therapy (ABC REBT) in reducing the psychological problems of golf athletes, especially athletes who are facing problem especially mental game and yips. Symptoms of this problem include anxiety and loss of self-confidence, shown through sweating and clumsy conditions when putting and chipping in critical situations. As a result, athletes face low self-confidence especially during major championships. In identifying the effectiveness of the module,the study conducted on the same athlete in previous years as respondents. This study also uses qualitative approach, involving three golf athletes. The views of coach who train them full time are also taken to support any changes in the results of the study. The theme of analysis and content analysis has been used. The findings show that the using of ABC REBT module treatment to overcome the mental game and the yips of golf athletes is effective in the long run. The result of theme analysis and content analysis reinforces the effectiveness of the ABC REBT treatment module on respondents. The result of this study are important in expanding the scope of counselling services in sports, and also proves the effectiveness of counselling approaches to athletes. Therefore, involvement of counselling practitioners in sports is also recommended. The article also illustrates the potential of cognitive and behavioural counselling approaches in reducing the problem.